Clinical environmental stressors and coping behaviors among undergraduate nursing students in Saudi Arabia: A cross-sectional study - Mona Rkhiyes Alanazi; Nouf Afit Aldhafeeri; Samah Saad Salem; Tarfah Mousa Jabari; Ryenad khalid Al Mengah (Elsevier, 2023)
Objectives: This study aimed to explore the level of stress, stressors sources, and coping strategies used among female Saudi undergraduate nursing students during their clinical practice. Methods: A cross-sectional design was used. Using a convenience sampling technique, female nursing students in Riyadh, Jeddah, and Alahsa who enrolled in clinical courses were recruited from a governmental university from January to May 2022. Data were collected using a self-report questionnaire including socio-demographic characteristics, the Perceived Stress Scale (PSS), and the Coping Behavior Inventory (CBI). Results: The degree of stress perceived by the 332 participants ranged from 3 to 99 (54.77 ± 0.95). Stress from assignments and workload was the most common type of stressor perceived by nursing students, with a score of 2.61 ± 0.94, followed by stress from the environment, with a score of 1.18 ± 0.47. Meanwhile, the students used staying optimistic as the most adopted strategy, with a score of 2.38 ± 0.95, followed by the transference strategy, a score of 2.36 ± 0.71, and the problem-solving strategy scored 2.35 ± 1.01. The coping strategy of avoidance is positively correlated with all of the stressor types (P < 0.01), while the problem-solving strategy is negatively correlated with stress from peers and daily life (r = −0.126, P < 0.05). Transference is positively correlated with stress from assignments and workload (r = 0.121, P < 0.05), and stress from teachers and nursing staff (r = 0.156, P < 0.01). Lastly, staying optimistic is negatively correlated with stress from taking care of patients (r = −0.149, P < 0.01), and with stress from lack of professional knowledge and skills (r = −0.245, P < 0.01). Conclusions: These research findings are significant for nursing educators to identify nursing students' main stressors and coping strategies used. Effective countermeasures should be taken to promote a healthy learning environment, decrease the level of stressors and improve students' coping strategies during clinical practice.